Floristic richness, structure and endemism of a piedmont forest in Zumba, Zamora Chinchipe, Ecuador (SCIÉNDO INGENIUM, 2025)
The piedmont forest is a transitional vegetation formation between lowland vegetation and the Andes. This research aimed to determine the floristic composition, structure and endemism of the tree component in a permanent plot of the piedmont forest in Zumba, province of Zamora Chinchipe. A permanent plot of one hectare was installed, subdivided into 25 sub-plots of 400 m². Individuals larger than 5 cm DBH were measured, tagged and identified, measuring DBH, total height, diameter and crown shape. Floristic diversity, endemism and structural parameters of the forest were calculated. Sixty two species from 52 genera and 29 families were recorded; the most diverse families were Rubiaceae, Lauraceae and Melastomataceae. The ecologically relevant species are Clethra parallelinervia, Alchornea glandulosa and Viburnum cf. obtectum. The diameter structure presents an inverted “J” distribution, typical of a recovering forest, with a basal area of ​​16.24 m²/ha and a volume of 84.18 m³/ha. The codominant stratum stands out with trees of 9 to 14 m, and the horizontal structure is characterized by interlaced canopies and forest gaps. Saurauia harlingii and Clethra parallelinervia are the endemic species recorded. Due to the high diversity and state of regeneration of this forest remnant, its conservation is necessary.
Keywords: Piemontane forest; floristic composition; structural parameters; diametric structure; structural profiles and endemism